The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Genesis of Successive Quasi-Linear Convective Systems over North China: Dynamical and Thermodynamic Forcing by a Cold Vortex, Complex Terrain, and Surface Boundaries - Yan Zhang; Rudi Xia; Jinfang Yin; Jianhua Sun; Linlin Zheng (Journal of Meteorological Research, 2026)

A bioinspired chitosan-polymer facilitated CO2 utilization under mild reaction conditions - Linlin Li; Jiang Zhao; Qingmei Ge; Yin-Hui Huang; Hang Cong; Wenfeng Zhao (Biomass and Bioenergy, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Research on forecasting and analysis methods for ship deck icing in polar regions - Zhenze Yang; Zhenju Chuang; Linlin Yin; Yijie Zhao; Nan Gao (Ocean Engineering, 2026)

Iron-induced charge density redistribution of medium entropy alloys for ampere-level seawater electrolysis - Luyu Liu; Xiang Ding; Jun Xiang; Haotian Qin; Siyuan Tang; Linlin Xu; Jianling Dong; Yin Yin; Nan Jiang; Xinchun Yang; Fuzhan Song (Fuel, 2026)

Meteorological observation research based on an improved EfficientNetV2 model - Haozheng Yin; Yu Cao; Linlin Liu; Dan Chen; Qiong Zhang (Environmental Modelling & Software, 2026)

Physiological changes in carbon sequestration and lipid production characteristics of microalgae under high CO2 domestication - Xinqing Gao; Longfei Yuan; Hui Yin YEONG; Guangze Lv; Xiangya Zhang; Xiaodong Zhang; Linlin Zhang; Jianjun Liao (Environmental Science and Pollution Research, 2026)

Numerical Investigation of Wind-Wave Loads on Nuclear-Powered Icebreakers in Tornado Extreme Environments - Linlin Yin; Zhenju Chuang; Ankang Hu; Zhenze Yang; Jixu Yang (Journal of Marine Science and Engineering, 2025)
As critical assets for polar development and global strategy, nuclear-powered icebreakers necessitate rigorous safety research under extreme meteorological conditions. Evaluating their reliability under tornado loads is essential to ensure sustainable Arctic operations. This study employed numerical methods to solve tornado loads and assess the safety performance of an icebreaker subjected to tornado-induced loads. Tornado loads at varying azimuth angles were solved using a modified Ward-type simulator, while wave loads under tornado conditions were determined by a numerical wave model. The results demonstrated that the tornado applied the maximum wind load on the structure at a 0° azimuth angle. The total wind load was reduced by approximately 39% at a 60° azimuth angle. The tornado-induced moment on the ship exhibited a strongly nonlinear relationship with the azimuth angle. The maximum total moment occurred at a 15° azimuth angle, whereas the minimum total moment was observed at a 90° azimuth angle, where the hull experienced minimal wind loads.

Remediation of alkaline cadmium (Cd) contaminated soil through biochar combined with organic fertilizer application - Linlin Liu; Jie Hu; Di Miao; Wenxin Yin; Wenping Sun; Lianglun Sun; Meizhen Tang (Environmental Geochemistry and Health, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Photocatalytic chitosan/hydroxypropyl methylcellulose-based multifunctional film incorporated with chlorophyll-TiO2@carbon sphere dual heterojunction and L-arginine for banana preservation - Haoran Wang; Wei Ji; Feng Xiao; Yewen Xiao; Linlin Li; Xia Shu; Hualin Wang; Jun Yin (Chemical Engineering Journal, 2025)

Green methanol synthesis from renewable energy integrated with compressed CO2 energy storage and waste-based systems: Thermodynamic, economic and environmental assessment - Manfeng Li; Shipeng Yin; Guofeng Zhou; Suping Li; Bo Peng; Linlin Zhang; Tianbiao He (Journal of Cleaner Production, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Dissolved organic matter sources in urban outfall water before and during rainfall, indicated via its fluorescence fingerprinting - Haojie Yin; Tao Huang; Bo Wang; Yingying Zhang; Jiawei Hu; Linlin Zhu; Kaining Chen (Applied Geochemistry, 2025)

Mutual influence of bubble evolution and seepage flow in heterogeneous porous matrices - Linlin Gu; Shicai Sun; Rundong Zhang; Rongtao Yan; Yonghao Yin; Guanru Gong (Gas Science and Engineering, 2025)

One-step synthesis of K3PO4-activated phosphorus-enriched carbons for enhanced carbon capture - Yue Zhi; Yujia Yin; Quji Ciren; Qiang Xiao; Leihong Zhao; Muslum Demir; Utku Bulut Simsek; Xin Hu; Linlin Wang (Journal of Environmental Chemical Engineering, 2025)

Cover Image - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
The cover image is based on the article Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control by Zhipeng Gao et al., https://doi.org/10.1111/raq.70024 . image

Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
Aquaculture is essential for meeting future demands for food, yet it faces significant losses from infectious bacterial diseases. Aquaculture has recently been critically imperiled by the emergence of multi‐drug‐resistant bacteria, as it relies significantly on the use of antibiotics for prevention and treatment. The emergence of multidrug‐resistant bacteria poses a critical threat to aquaculture, which heavily relies on antibiotics for prevention and treatment. Bacteriophage (phage) therapy has regained attention with the spread of drug‐resistant bacteria. Phages are viruses that specifically infect bacteria and archaea. As a promising therapeutic strategy for aquatic bacterial diseases, phage therapy offers strong specificity, low resistance potential, rapid metabolism, ease of development, and cost‐effectiveness. In this review, we discuss the advantages, opportunities, and challenges of phage therapy, summarizing the status of research and highlighting emerging technologies aimed at enhancing phage therapy in aquaculture. Finally, the review looks to the future, identifying scientific and technological advances necessary to establish phage therapy as a viable and universal alternative to antibiotics in aquaculture.

Development of a colorimetric sensor array with weighted RGB strategy for quality differentiation of Anji white tea - Qilin Xu; Xianggang Yin; Xinyi Huo; Xiaohan Zhao; Linlin Wu; Yifeng Zhou; Jun Huang (Journal of Food Engineering, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Pore structure-dependent adsorption of monochloramine by activated carbon - Xin Cheng; Xiaojun Miao; Linlin Li; Xueyan Xue; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2025)

Utilizing zeolitic imidazolate framework-8 for enhanced carbon dioxide/methane separation and improved carbon dioxide methanation performance - Weiqi Zhang; Xin Kong; Linlin Bo; Delin Yin; Zhichun Zhang; Xiaojun Fan; Hongping Chen; Jin Yuan (Bioresource Technology, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Magnetic resonance spectroscopy for discriminating primary angiitis of the central nervous system from gliomas and lymphomas - Ping Lu; Lingyun Cui; Lulin Zhang; Huabing wang; Linlin yin; Decai Tian; Xinghu Zhang (Acta Neurologica Belgica, 2025)

A highly sensitive fluorescent probe based on functionalised ionic liquids for timely detection of trace Hg2+ and CH3Hg+ in food - Siying Che; Yao Fan; Xuemei Hu; Linlin Yin; Haiyan Fu; Yuanbin She (Food Chemistry, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

In Utero Exposure to Lead is Associated with Neural Tube Defects via Disturbing the Expression of Endocannabinoid Retrograde Signaling-Related Genes - Tian Tian; Huijun Dong; Shengju Yin; Mengyuan Liu; Yongyan Chen; Kuanhui Xiang; Linlin Wang; Jie Qiao; Aiguo Ren (Exposure and Health, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

In vitro and in vivo anti-oomycetes activities and mechanisms of linalool against Saprolegnia ferax - Tao Tang; Weiming Zhong; Linlin Yang; Mingwang He; Sifan Jiang; Dan Yin; Jiajing Guo; Zhipeng Gao (Aquaculture, 2024)

Advancing ocean subsurface thermal structure estimation in the Pacific Ocean: A multi-model ensemble machine learning approach - Jifeng Qi; Linlin Zhang; Baoshu Yin; Delei Li; Bowen Xie; Guimin Sun (Dynamics of Atmospheres and Oceans, 2023)

Manipulating electron redistribution induced by asymmetric coordination for electrocatalytic water oxidation at a high current density - Sheng Zhao; Feng Hu; Lijie Yin; Linlin Li; Shengjie Peng (Science Bulletin, 2023)

Elevation-dependent tree growth response to recent warming and drought on eastern Tibetan Plateau - Dingcai Yin; Xiaohua Gou; Haijiang Yang; Kai Wang; Jie Liu; Yiran Zhang; Linlin Gao (Climatic Change, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Real-time monitoring of mercury(II) in water and food samples using a quinoline-based ionic probe - Siying Che; Linlin Yin; Ming Chen; Yao Fan; Anni Xu; Chunsong Zhou; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

Efflux pumps activation caused by mercury contamination prompts antibiotic resistance and pathogen's virulence under ambient and elevated CO2 concentration - Linlin Qiu; Yabo Wang; Wenchao Du; Fuxun Ai; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

CuO nanosheets incorporated scrap steel slag coupled with persulfate catalysts for high-efficient degradation of sulfonamide from water - Keke Yin; Linlin Hao; Guiju Li (Environmental Research, 2023)

LncRNA OIP5-AS1 Mitigates Bupivacaine-Induced Neurotoxicity in Dorsal Root Ganglion Neurons Through Regulating NFAT5 Expression via Sponging miR-34b - Yina Yin; Min Ma; Junxiao Chang; Yufang Kong; Linlin Rui; Guoqiang Chu; Keliang Zhang (Neurotoxicity Research, 2022)

Prenatal exposure to silver is associated with an elevated risk for neural tube defects: a case–control study - Xin Pi; Chengrong Wang; Di Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Wentao Yue; Chenghong Yin; Aiguo Ren (Environmental Science and Pollution Research, 2022)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

Utilization of serum procalcitonin as a biomarker in the diagnosis and treatment of children with bacterial hospital-acquired pneumonia - Wenlong Wang; Yitang Zhu; Linlin Yin; Yaoyao Deng; Guoxian Chu; Supin Liu (Molecular and Cellular Biochemistry, 2021)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Effect of supersaturation on the oral bioavailability of paclitaxel/polymer amorphous solid dispersion - Linlin Miao; Yuheng Liang; Wenli Pan; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Xing Tang (Drug Delivery and Translational Research, 2019)

Insight into the effects of biochar as adsorbent and microwave receptor from one-step microwave pyrolysis of sewage sludge - Jun Zhang; Yu Tian; Linlin Yin; Jie Zhang; Jörg E. Drewes (Environmental Science and Pollution Research, 2018)

Co-Delivery of Doxorubicin and Survivin shRNA-Expressing Plasmid Via Microenvironment-Responsive Dendritic Mesoporous Silica Nanoparticles for Synergistic Cancer Therapy - Zhengxiong Li; Linlin Zhang; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2017)

Investigation on the removal of H2S from microwave pyrolysis of sewage sludge by an integrated two-stage system - Jun Zhang; Yu Tian; Linlin Yin; Wei Zuo; Zhenlong Gong; Jie Zhang (Environmental Science and Pollution Research, 2017)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

A ras GTPase-activating protein-binding protein, TaG3BP, associated with the modulation of male fertility in a thermo-sensitive cytoplasmic male sterile wheat line - Linlin Zhou; Guoqi Song; Beiru He; Yin-Gang Hu (Molecular Genetics and Genomics, 2011)